It’s the workflows, stupid! What is required to make “offsetting” work for the open access transition - Geschuhn, Kai Karin; Stone, Graham (Septentrio Conference Series, 2017)
Watch the VIDEO here. Presenter – Kai Geschuhn The conference contribution makes the case for a stronger engagement of libraries and consortia when it comes to negotiating and drafting offsetting agreements. Two workshops organised by the Efficiencies and Standards for Article Charges (ESAC) initiative in 2016 and 2017 have shown a clear need for an improvement of the current workflows and processes between academic institutions and their libraries and the publishers in terms of author identification, metadata exchange, and invoicing. Publishers need to invest in their editorial systems while institutions need to get a clearer understanding of the strategic goal of offsetting. To this purpose, strategic and practical elements, which should be included in the agreements, will be introduced. Firstly, the “Joint understanding of offsetting”, launched in 2016, will be discussed. This introduces the ‘pay-as-you-publish’ model as a transitional pathway of the agreements. Secondly, the contribution proposes a set of recommendations for article workflows and services between institutions and publishers, based on a draft document, which was produced as part of the 2nd ESAC workshop in March 2017. These recommendations should be seen as a minimum set of practical and formal requirements for offsetting agreements and are necessary to make any publication based open access business model work. The conference contribution is based on an article currently under review for the November 2017 issue of the journal “UKSG Insights”.